Analysis of Cognitive Process Dimensions by Problem-Based Learning on Globalization Theme - Ernawati, Ninik; Masyhud, M. Sulthon; Dyah Prastiti, Tri (International Journal of Scientific Research and Management (IJSRM), 2022)
Globalization brings changes to the behavior of human life. One of the benefits of globalization is that students are easy to get learning material. Students are easy to complete learning material for factual, conceptual, and procedural knowledge. The negative impact of globalization can cause changes in negative behavior of students. Problem-Based Learning is an innovative learning model. The purpose of the study was to analyze Problem-Based Learning as its impact on cognitive processes dimensions. The research design is qualitative descriptive. The study was conducted on students of Madrasah  Ibtidaiyah public school/ elementary schools with the theme of Globalization by applying Problem-Based Learning. The study involved as many as  Madrasah Ibtidaiyah students. Dimensions of cognitive processes that are measured are the dimensions of knowledge (C1), the dimensions of understanding (C2), the dimensions of application (C3), the dimensions of analysis (C4), the dimensions of evaluation (C5), and the dimensions of creating (C6). Data analysis was performed by using method with statistical analysis t-test to see differences in trends of each dimension of the cognitive process under study and qualitative descriptive analysis through interviews and image analysis. The results showed that there were differences in each dimension of cognitive processes and there was a significant increase from the dimensions of low cognitive processes to medium and high cognitive processes in the application of Problem-Based Learning.